Building a professional global disaster response team at an academic health-care institution: the professionalisation of humanitarian health-care workers - H Cranmer; M Aschkenasay (Elsevier, 2014)
Background: The numbers of individuals affected by disasters and conflict are on the rise, similarly are the numbers of clinicans who seek to help. Although health-care workers want to provide immediate clinical care-as in field hospitals-disaster response requires a comprehensive set of knowledge, skills, and behaviour not taught in medical and nursing schools. With competency-based training and a vetted and credentialed workforce, academic medical institutions have the opportunity to augment emergency response for humanitiarian aid organisations. We aim to describe the minimum standards for building a professional disaster response team within an academic medical institution. Methods: Through literature review and key informant interviews, we built a database to describe emergency response experience in 21 countries within 25 national and international aid organisations, governments, and academic universities. We created a checklist and applied this to responses for sudden onset and chronic crises. Key variables included deployment parameters, credentialing procedures, competency or skillset requirements, predeployment and postdeployment preparation, and types of organisational support. Findings: We found large variation between organisations for emergency response, including the credentialling process, definition of competency or skillsets, implementation of deployment, and the extent of organisational support. From this analysis, we created a set of minimum standards for deployment, including physical and mental fitness, previous professional experience, team-based response, appropriate flexible skillset, approval or vetting by direct supervisors, initial or duration of availability, cultural or language competency, self reliance in austere conditions, communication skills, briefing and debriefing participation, and support from organisation. Interpretation: Minimum standards and guidelines for institutions deploying health-care workers to disasters is a key step in professionalisation. Funding: None.